Enhancing Students' Learning Interest through the Use of Vascak Physics Animation as a Physics Learning Medium - Syifa, Annisa; Mastul, Al-Rashiff Hamjilani (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2023)
Technology has made various activities easier, including the process of teaching and learning in schools. The development of diverse technology-assisted learning media can enhance students' learning interest. Learning activities can be conducted in various ways, one of which is through the use of instructional media. Vascak Physics Animation is an interactive learning medium developed to support physics education. This media utilizes captivating animations, simulations, and visualizations to help students better understand physics concepts. Moreover, students can visually observe how physics concepts operate in real-life situations. The animations can also be customized with various parameters, enabling students to conduct virtual experiments and observe the effects of changes in the studied phenomena. By practicing with virtual physics labs, students are able to engage in practical activities and review learned materials anytime and anywhere. The development of innovative and varied learning media is expected to increase students' learning interest and academic achievements.